IMPLEMENTATION CHALLENGES AND IMPACTS OF IFRS S1 AND IFRS S2 ON SUSTAINABILITY REPORTING QUALITY: A SYSTEMATIC REVIEW OF THE MINING INDUSTRY (2022-2024) - Gilang Surya Pratama; Kornelia Serafina; Inviolata Dua Sareng; Yanuar Ramadhan (ZILLZELL MEDIA PRIMA, 2025)
The introduction of IFRS S1 and IFRS S2 represents a pivotal shift in sustainability reporting, especially in the mining sector. This study systematically reviews the challenges and impacts of these standards on reporting quality from 2022 to 2024. It highlights that larger mining companies have shown progress in aligning their reports with the new standards, whereas medium and smaller enterprises face barriers like resource constraints and technical limitations. The findings indicate improvements in governance and risk management, driven by the comprehensive disclosure requirements of the standards. However, significant gaps persist, particularly in quantitative metrics such as scope 3 emissions reporting. The implementation costs are substantial but are offset by enhanced market valuations and stakeholder trust for companies that comply effectively. To address these challenges, companies must adopt advanced technologies, strengthen their governance frameworks, and foster stakeholder collaboration. This study emphasizes the need for industry-specific implementation guidelines and capacity-building initiatives, particularly in emerging markets, to achieve widespread compliance and uniform reporting quality.